The Indo-Pacific Child Trafficking Dynamics: Islamic and Cultural Viewpoints - Firdaus, Firdaus; Mursal; Syaflin Halim; Desminar; Ramadhansyah, Fery (KARSA Journal of Social and Islamic Culture, 2023)
This research reviews the child protection paradigm in the Indo-Pacific region, especially in Indonesia, by highlighting the imbalance between the status of developed countries and the need to develop thinking and implementation of Islamic law. The research results show that understanding of Islamic law regarding child protection is in line with human rights principles and the Child Protection Law. Factors influencing child trafficking involve the social and economic conditions of countries, while movements, interactions, and changes in child trafficking systems reflect the complexity of this problem. Child protection agencies highlight the mode of child trafficking through online channels and loose borders, with the main obstacles being differences in levels of understanding and lack of coordination between countries. Parents emphasized education, the role of the community in prevention, personal experiences related to concerns about children's safety, and participation in children's education. Parents' hopes include strengthening legal and policy frameworks involving cultural values and Islamic law, as well as community support for more effective prevention efforts. In conclusion, this research provides critical insight into the role of Islamic law and cooperation between government and society in protecting children from trafficking in the Indo-Pacific region.